Relationship of personal and professional identity in high school students - Natalia A. Rozhdestvenskaya; Igor L. Mozharovsky; Veronika V. Makaryan (Национальный психологический журнал, 2018)
Background. Connected with the changes that have taken place in the labour market in the last decades, psychologists are faced with the scientific and practical task of improving vocational guidance work with high school students using new programs to develop their personal and professional identity. Objective. Based on the epigenetic theory of development the objective is to generalize and systematize the theoretical and empirical studies of personal and professional identity in adolescents aged 15–16, establish new empirical facts, verify the results already obtained and develop practical recommendations for improving vocational guidance counseling for high school students. Design. Some features of the relationship between personal and professional identity of high school students aged 15–16 were studied. First of all, the relationship of personal identity with age was studied. In the course of the research, such methods as studying personal identity of D. Marcia modified by V.R. Orestova and O.A. Karabanova and methods of professional identity of A.A. Azbel and A.G. Gretsov were used. The methods were disseminated among 158 respondents, and the questionnaires filled by 132 respondents turned out to be suitable for processing. Research Results. Several hypotheses were put forward: 1. The level of personal identity development is significantly associated with the age of high school students. 16-year-old 10th-graders outnumber 15-year-old 9th-graders. Between the age groups, significant differences were identified (p = 0.048), so the hypothesis is confirmed. 2. The majority of 15-year-old 9th-graders (63.3%) and 16-year-old 10th-graders (62.2%) who go to Moscow schools have a status of a moratorium. The hypothesis is confirmed. 3. For the age of 15-16 years, the dynamics of professional identity is absent. The hypothesis is confirmed. The differences between adolescents of 15 and 16 years in this parameter are not statistically significant (p = 0.993). 4. The level of personal and professional identity development is higher in females than in males. The hypothesis was not confirmed as the differences between females and males are not significant (p = 0.122), (p = 0.928). Conclusion. As a result of generalization of theoretical and empirical data, an author’s approach to improving vocational guidance work with high school students is proposed.